2019
DOI: 10.1080/17453674.2018.1561614
|View full text |Cite
|
Sign up to set email alerts
|

Early palmar plate fixation of distal radius fractures may benefit patients aged 50 years or older: a randomized trial comparing 2 different treatment protocols

Abstract: Background and purpose — There is no consensus regarding optimal treatment of displaced distal radius fractures (DRFs). We compared the results of 2 treatment protocols: early palmar plating vs. primary nonoperative treatment of displaced DRFs. Patients and methods — We performed a prospective randomized controlled study including 80 patients aged ≥ 50 years with dorsally displaced DRFs, excluding AO type C3 fractures. Patients were randomized to undergo either immediate surgery with palmar plating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(85 citation statements)
references
References 25 publications
7
77
0
1
Order By: Relevance
“…The 8 RCTs 31,35,36,38,[46][47][48][49] included 656 patients (29.1%), of whom 322 were treated operatively and 334 nonoperatively. The weighted mean age was 67 years (67 years in the operative group and 68 years in the nonoperative group).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 8 RCTs 31,35,36,38,[46][47][48][49] included 656 patients (29.1%), of whom 322 were treated operatively and 334 nonoperatively. The weighted mean age was 67 years (67 years in the operative group and 68 years in the nonoperative group).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Complication rate was reported in 19 studies, including 8 RCTs 31,35,36,38,[46][47][48][49] and 11 observational studies. [32][33][34]37,[39][40][41][42]45,50,51 The overall pooled effect showed no difference in complication rate between operative and nonoperative treatment with an RR of 1.03 (95% CI, 0.69- For studies that did not present characteristics for treatment groups separately, the numbers presented are for the overall study group, and the cells are merged.…”
Section: Primary Outcome Measuresmentioning
confidence: 99%
“…Of 290 potentially eligible articles, most were excluded due to duplicates and lack of relevance. Finally, 11 studies [4,6,7,9,[16][17][18][19][20][21][22], including five RCTs [6,7,9,20,21], five retrospective studies [4,[16][17][18]22], and one prospective study [19], satisfied the inclusion criteria after screening and assessment. The studies were published from 2009 to 2019, most within the past 5 years.…”
Section: Including Studiesmentioning
confidence: 99%
“…Aktekin et al 11 showed that wrist extension and ulnar deviation were significantly better in patients treated with EFP compared with casted patients who were aged 65 years or older. Sirniö et al 9 reported no changes in pinning. Our results are more similar to previous investigations 10,12,13 that reported no association between fracture alignment and PROs in older patients.…”
Section: Discussionmentioning
confidence: 95%
“…To our knowledge, there are only 8 published reports of 24-month or longer outcomes in older populations, and, of those, only 2 reported intermediate time points. [8][9][10][11][12][13][14]16 Furthermore, no study conducted a concurrent comparison of all 4 currently accepted treatments. Arora et al 8 found no changes in radiographic alignment between 12-week and 4-year assessments of patients aged 70 years and older treated with casting or open reduction and internal fixation.…”
Section: Discussionmentioning
confidence: 99%